An investigation of seven other publications by the first author of a retracted paper due to doubts about data integrity. (June 2021) - Bordewijk, Esmée M.; Li, Wentao; Gurrin, Lyle C.; Thornton, Jim G.; van Wely, Madelon; Mol, Ben W.
Abstract: Background: In 2019, a randomized controlled trial (RCT) authored by Dr. Ismail was retracted due to concerns about data integrity. Since there are no policies in place to investigate other publications of authors of retracted studies, we investigated Dr. Ismail's other trials. Methods: We searched for RCTs authored by Dr. Ismail. We made pairwise comparisons of values in baseline and outcome tables between trials. We assessed whether the distributions of baseline characteristics were compatible with properly conducted randomization, using Monte Carlo simulations and the Kolmogorov-Smirnov test. We read the publications carefully for unusual features. Results: Dr. Ismail was author in eight published and one unpublished trial. In three of his first author studies we found multiple identical values in the baseline and/or outcome tables from different trials. At least some of the trials were unlikely to have followed a proper randomization process. There were a number of other unusual features in the papers we reviewed. Conclusions: It is probable that other trials published by Dr. Ismail contain questionable data. We call for a thorough investigation of the original trial data and related official documents. Our exercise suggests that the practice to assess research integrity should include all publications of authors with retracted fabricated articles.